Maternal Mortality: Paradigm Shift in Nepal - Bhadari, TR; Dangal, G (Nepal Journal of Obstetrics and Gynaecology, 2014)
Achieving Millennium Development Goal (MDG) 5 still remains a challenge to Nepal. It is necessary to collect reliable evidence on maternal health for tackling MDG 5 with limited resources. A continuous assessment of maternal mortality is required to assure the progress towards the MDG 5. This study aims to assess the results of the different studies on maternal mortality in Nepal. The results published in PubMed, Lancet, Medline, WHO and Google Scholar web pages from 1990 to 2012 have been utilized to prepare this paper. In spite of the low proportion of births attended by skilled persons and institutional delivery, the maternal mortality ratio (MMR) in Nepal has declined drastically between the years 1990 and 2011, from 850 to 229 deaths per 100,000 live births. In recent years, Nepal is also reaching progress in different maternal health indicators such as mothers receiving antenatal care from skilled providers (60%- up from 24% in 1996). More than one-third births in the past five years have been assisted by skilled care providers. Nearly, 45% of women received postnatal care for their last birth in the first two days after delivery, 38% of women is aware of abortion which has been legalized since 2003. Though maternal health is a priority agenda of Nepal among the policy makers and the country is likely to achieve Millennium Development Goal 5 by the year 2015, there is still a wide gap between policies and charted targets, and the real accessibility and availability of the quality health services. DOI: http://www.dx.doi.org/10.3126/njog.v7i2.11132 Nepal Journal of Obstetrics and Gynaecology / Vol 7 / No. 2 / Issue 14 / July-Dec, 2012 / 3-8